Understudied and underaddressed: Femicide, an extreme form of violence against women and girls - Reis, Chen; Meyer, Sarah R. (PLOS Medicine, 2024)
Little is known about the prevalence and dynamics of femicide, a persistent form of violence against women and girls, due to challenges associated with its documentation. Research by Abrahams and colleagues comparing rates of femicide in South Africa over 18 years, however, suggests that femicide is preventable.